Control of Rigid Ryegrass in Australian Wheat Production with Pyroxasulfone. (June 2014) - Boutsalis, Peter; Gill, Gurjeet S.; Preston, Christopher
Abstract : In Australia, most wheat is sown in a no-till system without prior cultivation where herbicides are applied prior to sowing and incorporated by the planter. Trifluralin has been the most widely used PRE herbicide to control rigid ryegrass. The objective of this research was to determine crop safety and efficacy of alternative mechanism of action PRE herbicides for rigid ryegrass control in no-till wheat production. Pyroxasulfone achieved 98% control with PRE applications. The alternative PRE herbicides tested alone and in mixtures occasionally resulted in a significant reduction in wheat emergence but not crop yield. Trifluralin treatments failed at sites having trifluralin-resistant rigid ryegrass. Pyroxasulfone and prosulfocarb plus S -metolachlor were effective for control of rigid ryegrass across all trials with control ranging from 64 to 94%. This research demonstrated that PRE applications of herbicides other than trifluralin such as pyroxasulfone and prosulfocarb plus S -metolachlor can be safely and effectively used to control rigid ryegrass in no-till wheat.